Reassessment of the Influence of Socio-demographic Variables on Hotel Choice during Pandemic - Duarte, Paulo; Estevão, Cristina; Campón-Cerro, Ana María; Costa, Carlos; Cabral, Adília (Journal of Tourism, Sustainability and Well-being, 2023)
The hospitality and travel sector has been one of the most affected sectors by Covid-19, which has resulted in a significant increase in the literature addressing the impact of the health crisis on tourism activities and tourists’ perceptions and behaviours. Traditionally, socio-demographic variables have been instrumental in understanding consumers’ needs and desires. However, during the pandemic, it has been unveiled that social and economic profiles have started to influence how tourists make decisions. Since studies on the changes in hotel choice during and after Covid-19 are still scarce, this article aims to assess the influence of socio-demographic variables on hotel choice based on data collected during the peak phase of the Covid-19 pandemic. A quantitative study was conducted using an online questionnaire that reached an international sample of 1113 individuals. The ANOVA and the t-test analysis results point out that socio-demographic variables under study are responsible for several differences in the evaluation of hotels. These findings reinforce socio-demographic attributes’ capability to understand customers’ preferences and decision-making despite the context.